PENGARUH CUSTOMER EXPERIENCE DAN HOTEL ATMOSPHERE TERHADAP KEPUTUSAN MENGINAP DI SWISSOTEL, JAKARTA UTARA - CHRISTIAN GUNAWAN; JOECELIND GABRIELA; VALENCIA CHATLYN GANI; JULIANA . (LP2MTBM MAKARIOZ, 2020)
The research objective is to analyze the effect of customer experience on staying decisions at Swissotel North Jakarta, toanalyze the effect of hotel atmosphere on staying decisions at Swissotel North Jakarta, and to analyze the effect of customerexperience and hotel atmosphere on staying decisions at Swissotel North Jakarta. The research method uses quantitativedescriptive. The object of research at the Swissotel Hotel North Jakarta with simple random sampling technique, and datacollection using a questionnaire. The sampling technique uses probability sampling with the type of simple random sampling.Where in this study using the method of the number of variables used multiplied by five. Thus, the sample in this study was130 respondents. Data analysis was performed using SPSS ver.25 to get results that customer experience has a positiveinfluence on stay decisions, hotel atmosphere has a positive and significant impact on stay decisions, and customerexperience and hotel atmosphere has a positive and significant influence on stay decisions.